A History of Navajo Nation Education : Disentangling Our Sovereign Body - Greyeyes, Wendy Shelly, 1978- (Book collections on Project MUSE., 2022)
"This book sheds light on the tangle of federal and state education programs that have been imposed on Navajo territories, and on the ongoing efforts by tribal communities to transfer state authority over Dine education to the Navajo Nation. The complex and confusing educational system, influenced by colonial pressures and tribal resistance, limits movements towards a unified tribal educational sovereign goal. Providing both a historical overview and an in-depth view of the current situation, Greyeyes argues that in order to decolonize education, tribal communities must first "unwind the binds of jurisdictions, codes, policies, and procedures" created by this tangle of jurisdictions and authorities. The book covers the evolution of key players of the central tribal councils, council delegates, local chapters, school boards, tribal chairs and presidents, and the emerging tribal education department administrators through existing government documents, reports, and interviews. The final two chapters provide a concise depiction of current conditions, challenges, and opportunity for future change in the quest for educational sovereignty at the Navajo Nation. Kevin Washburn, former Assistant Secretary of Indian Affairs, will write a foreword for the book"--